Correlation between small‐scale methylation changes and gene expression during the development of myopia. Issue 1 (27th December 2021) - Thomson, Kate; Game, Jeremy; Karouta, Cindy; Morgan, Ian G.; Ashby, Regan
Abstract: Visually induced changes in the expression of early growth response‐1 ( EGR1 ), FBJ osteosarcoma oncogene ( FOS ), and NGFI‐A binding protein‐2 ( NAB2 ) appear to form a part of a retinal network fundamental to ocular growth regulation, and thus, the development of myopia (short‐sightedness). However, it is unclear how environmental (visual) cues are translated into these molecular changes. One possibility is through epigenetic modifications such as DNA methylation, a known regulator of such processes. By sequencing bisulfite‐converted DNA amplicons, this study examined whether changes in DNA methylation occur within specific regulatory and promoter regions of EGR1, FOS, and NAB2 during the periods of increased and decreased ocular growth in chicks. Visually induced changes in ocular growth rates were associated with single‐point, but not large‐scale, shifts in methylation levels within the investigated regions. Analysis of methylation pattern variability (entropy) demonstrated that the observed methylation changes are occurring within small subpopulations of retinal cells. This concurs with previous observations that EGR1 and FOS are differentially regulated at the peptide level within specific retinal cell types. Together, the findings of this study support a potential role for DNA methylation in the translation of external visual cues into molecular changes critical for ocular growth regulation and myopia development.